On the Paradigmatic Conception of the Physical - Kıymaz, Tufan (Problemos, 2021)
What “physical” means is sometimes clarified by appealing to paradigmatically physical objects, properties, or phenomena. This move is not entirely unmotivated. The most basic intuition behind physicalism can be identified as that we, as conscious beings, are not ontologically special: we are, ultimately, like all these inanimate and unconscious things; we do not exemplify any mysterious properties that are categorically over and above all the properties that are exemplified by ordinary things like chairs or rocks or their constituents. And, according to the dualists, we are, in terms of substance or property, metaphysically different from chairs, rocks, and the like. The kind of conception of the physical that refers to paradigm cases of the physical is in line with this disagreement in intuition between the physicalist and the dualist. Trying to conceptualize the physical based on some paradigmatically physical objects or phenomena, I argue, however, is a dead-end.